The long-term effectiveness of dialysis, kidney transplantation and pancreas transplantation for patients with diabetes mellitus and renal failure: A decision analysis. - Knoll, Gregory Allan. (University of Ottawa (Canada), 2002)
Background. Diabetics with renal failure have several treatment options including cadaveric (CKT) or living (LKT) kidney transplantation, simultaneous pancreas-kidney transplantation (SPKT), pancreas transplantation after kidney transplantation (PAKT) or dialysis. The objective was to determine the most effective treatment strategy. Methods. Decision analysis comparing dialysis, CKT, LKT, PAKT and SPKT. Model probabilities were obtained from the medical literature and utilities were obtained using the standard gamble. The outcome measure was quality-adjusted life expectancy (quality-adjusted life years, QALYs). Results. LKT was associated with 10.29 QALYs; PAKT, 10.00 QALYs; SPKT, 9.09 QALYs; CKT, 6.53 QALYs; dialysis, 4.52 QALYs. The results were sensitive to several key variables. Conclusion. LKT is the most effective treatment strategy for diabetics with renal failure. However, PAKT is preferred for patients with severe metabolic complications of diabetes and for those patients who favor the kidney-pancreas health state over kidney transplantation alone.
Keywords: Health Sciences, Public Health.